A perspective on musical representations of folded protein nanostructures. Issue 1 (5th January 2021) - Franjou, Sebastian L; Milazzo, Mario; Yu, Chi-Hua; Buehler, Markus J
Abstract: Proteins are the building blocks of all life, creating materials as diverse as spider silk, cells, and hair, but also other countless functions from enzymes to drugs. Here we discuss a method to represent folded protein nanostructures as musical compositions. We explore different avenues of artistic creation, interpolating between human design, natural or evolutionary design, and designs from a deep recurrent network model that was trained against musical scores of known three-dimensional protein structures. Artistically, our work offers a new perspective on the limits of scientific understanding, and allows human players to interact with nanoscale phenomena, providing a tool for STEM outreach, and use of nanoscopic phenomena for artistic expression.